Soil transmitted helminthes infection among pregnant women in peri-urban areas of Ibadan, Nigeria: A cross-sectional study (2018)
"Background: Soil Transmitted Helminthes (STH) infection is an important public health problem in developing countries which adversely affects pregnant women and their newborn infants. The epidemiology of STH among pregnant women has not been fully explored in Nigeria. We examined the prevalence, intensity and risk factors of STH among antenatal care attendees in Ibadan. Methods: A cross sectional facility-based study was conducted among the 326 pregnant women attending antenatal care clinics in six selected Primary Health Care centers, in the peri-urban areas of Ibadan Oyo State. An interviewer administered questionnaire was used to obtain information on the socio-demographic, maternal, environmental characteristics and hygiene practices. Kato-Katz method was used to identify the presence of STH from stool samples. Data were analysed using chi-square and bivariate logistic analysis. Results: The overall prevalence of STH was 13.8%, 95% CI (10.0–17.7). Ascaris lumbricoides 12.8%, 95% CI (9.5–16.9) was the most prevalent followed by hookworm infection 0.6%, 95% CI (−0.2–0.15) and Trichuris trichiura 0.3%, 95% CI (−0.2–0.9). Majority of the infection were of light intensity (44 out of 45). Walking bare footed in the home environment increased the likelihood of being infected with STH [OR 1.93 95% CI (1.01–3.72) p=0.048] compared with women who wore shoes. Conclusion: STH infection is prevalent among pregnant women in the peri-urban region of Ibadan. Therefore public health interventions like active surveillance of STH and the prescription of deworming drugs will be beneficial for pregnant women. "